Study on the relationship between nephrotic syndrome and atopic diseases in childhood - Zheng, Yue; He, Xuehui; Hou, Ling; Wang, Xiuli; Zhao, Chengguang; Du, Yue (Frontiers in Pediatrics, 2022)
Objective: The present study aimed to explore the relationship between nephrotic syndrome and atopic diseases in childhood. Methods: From 2018 to 2019, 234 children with first-onset primary nephrotic syndrome （PNS） were selected for observation and long-term follow-up, and the clinical and laboratory data. To compare the levels of total serum IgE, histamine and bradykinin of the same children at the time of first onset, remission and relapse of PNS. The extent of podocyte foot process effacement was compared between the urinary protein negative-conversion group and the proteinuric group with the NS range.The correlation between the urine protein quantification and the extent of foot process effacement was also observed. Results: 1. The mean age of 234 children with first-onset PNS was 4.82±3.63 years, with a male to female ratio of 162/72. 2. There were 109 cases (46.58%) with concomitant atopic diseases (AD) and 151 cases (64.5%) with elevated levels of total serum IgE. There were 136 cases with recurrence during the follow-up, of which recurrence due to allergy-related factors was greater than that due to infection-related factors. 3. The total IgE and bradykinin serum levels were significantly higher in children with first-onset PNS and recurrent PNS compared with those in remission, and the differences were statistically significant (P < 0.05). The level of histamine in children with first-onset PNS was higher than that in children with remission (P < 0.05), and there was no significant difference in the level of histamine between children in the recurrence group and those in the remission group (P > 0.05). 4. There was no significant difference in the extent of foot process effacement between the urinary protein negative-conversion group and the proteinuric group with the NS range. Conclusion: There existed a high co-morbidity with AD in children with PNS, and allergy-related factors might be an important recurrence factor in children with PNS. The injury to the filtration barrier in MCD might not only be correlated with podocyte lesions but also with some serum permeability factors. Serum IgE, histamine, and bradykinin might be the plasma permeability factors in children with PNS.